Soliton structures for a generalized unstable space-time fractional nonlinear Schrodinger model in mathematical physics - Tariq, Kalim U.; Khater, Mostafa M. A.; Ilyas, Medhat; Rezazadeh, Hadi; İnç, Mustafa (World Scientific Publ Co Pte Ltd, 2024)
One of the most important physical models for describing the dynamics of optical soliton propagation in the theory of optical fibers is the nonlinear Schrodinger equation (NLSE). Since there are so many uses for ultrafast signal routing systems and brief light pulses in telecommunication, optical soliton propagation in nonlinear optical fibers is a subject of intense current interest. The conventional Khater approach and the extended direct algebraic method are used in this research to study a generalized unstable space-time fractional NLS model in mathematical physics. This leads to the discovery of solutions for the bright, dark, periodic, rational and elliptic functions. To illustrate the physical nature of the nonlinear model, the contour plots in 3D, 2D and 2D are produced by assigning the appropriate values to the arbitrary constants. Additionally, consideration is given to the stability analysis of the solutions to the governing equation. In the current era of communications network technology and nonlinear optics, the applied strategy appears to be a more potent and effective way for producing precise optical solutions to a number of various modern models of recent generations.
Keywords: Nonlinear Schrodinger equation; traveling wave solutions; optical fibers